Impact of the Digital Divide on Internet Access and Computer Usage Amongst College of Education Students in South-Western Nigeria - Shehu Ahmed Hassan (CV. Media Inti Teknologi, 2025)
This qualitative and exploratory case study aims to find out how 20 education students at the Federal College of Education (Special), Oyo State, and the College of Education, Iwo, Osun State, in Nigeria perceive and use the internet and ICT. Drawing upon a comprehensive review of existing literature and empirical data, this paper examines the multifaceted dimensions of the digital divide within higher education institutions specifically Colleges of Education in South-Western Nigeria. The study adopted stratified random sampling to gather information from respondents. The research identifies crucial factors that cause the digital divide in this context, including disparities in infrastructure, internet accessibility, digital literacy, and socioeconomic backgrounds. The research results show that only four out of twenty (20%) people own a computer and pay a hefty price for internet access, eighteen (90%) of the research participants provided favorable feedback on their experiences with the usage of computers and the Internet having a good impact on their life, Eighteen out of twenty (90%) expressed a desire for the establishment of computer centers within schools and libraries, the extension of current infrastructure, computer training, and decreased tariff prices, and Eighteen (90%) of the participants endorsed computer and Internet training. It can be concluded that disparities in computer use and internet access persist among College of Education students in Nigeria due to factors such as socioeconomic background, geographical location, and digital literacy levels. Such consequences not only affect students' academic performance but also have implications for their future employability in an increasingly digital job market.